THE COMPARATIVE ANALYSIS OF STOCK PRICE TRADING VOLUME ACTIVITY AND ABNORMAL RETURN BEFORE AND AFTER STOCK SPLIT (Empirical Study on Listed Companies in Indonesia Stock Exchange in 2009-2013) - KISWILDAN, GUSMANE; Purnomosidhi, Bambang (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
The purpose of this research are 1) To analyze the differences stock price before and after stock split, 2) To analyze the differences of trading volume activity before and after stock split, 3) To analyze the differences of abnormal return before and after stock split, and 4) To analyze the differences of stock price, trading volume activity, and abnormal return before and after stock split. The population of the research consists of the listed companies’ annual reports at Indonesia Stock Market during the period 2009 up to 2013. All of the companies taken as sample have conducted stock split. To examine the research hypothesis, the author using Paired Sample t-test to analyze the difference on stock price, trading volume activity, and stock abnormal return before and after stock split. The result of this research showed that 1) There is a difference of stock price before and after stock split, 2) There is a difference of trading volume activity before and after stock split, 3) There is a difference of abnormal return before and after stock split, and 4) There is a difference of stock price, trading volume activity, and abnormal return before and after stock split. Keywords: stock split, stock price, abnormal return, trading volume activity.